Long-Term Outcomes and Predictors of Childhood-Onset Schizophrenia: A Naturalistic Study of 6-year Follow-Up in China - Liangrong, Zheng; Guican, Zhang; Qi, Zhu; Weirui, Yang; Yaqi, Zhang; Tong, Li; Wenjing, Liang; Ming, Zhang; Nianhong, Guan (Frontiers in Psychiatry, 2021)
Objectives: The long-term outcome of childhood-onset schizophrenia (COS) and its influencing factors remain unclear. The current study aimed to assess the long-term outcomes of COS and identify possible outcome predictors. Method: We retrospectively investigated 276 patients with COS. Diagnosis made according to the ICD-10 criteria for schizophrenia, and the age of the first onset was ≤14 years. Follow-up was completed for 170 patients, with a median follow-up period of 5.6 years. Outcome variables included occupational/education status and readmission. Spearman correlation was performed to assess the relationship between predictors and outcome variables. Binary logistic regression was conducted to detect possible predictor variables for outcome variables. Results: At the end of the follow-up, 89 patients (52.3%) were at school, 70 patients (41.2%) were employed, and only 11 patients (6.5%) were dropped out of school or unemployed. The duration to the first admission and depressive symptoms were identified as predictors of occupational/educational status. The length of follow-up and obsessive-compulsive symptoms (OCS) were distinguished as predictors of readmission. Duration to the first admission and length of follow-up were risk factors, and depressive symptoms and OCS were protective factors for the outcomes of COS. Conclusion: We found a favorable long-term outcome on occupational/education status in COS, and depressive symptoms and OCS may be associated with more positive long-term outcomes in COS. Our findings suggest that COS patients may benefit from early intervention and require appropriate treatment.